Menopon picicola: a new junior synonym of Menacanthus pici (Insecta: Phthiraptera: Menoponidae) - Palma, Ricardo L.; Galloway, Terry D. (Zootaxa, 2021)
Packard (1873) described Menopon picicola as a new species, based on ten lice taken from two species of woodpeckers of the genus Picoides—P. arcticus (Swainson, 1832) and P. dorsalis Baird, 1858—collected in Wyoming, U.S.A. in August 1872. Considering that (1) Packard (1873) neither designated a holotype nor a single type host, (2) his type material is most likely lost, and (3) no additional lice from either of those two species of Picoides have been reported in the literature, the taxonomic status of Menopon picicola has not been confirmed.